ARTICLE REVIEW: HARASSMENT, VIOLENCE, STRESS AND BURNOUT AT WORK, BY PEDRO GUILHERME BASSO MACHADO - Cicero da Silva, Luciano; Augusto Rodrigues Alves, Álefe; Tomael, Cassiana; Henrique Ferreira Manso, Paulo; Rodrigues Alves, Valquíria (Revista Gênero e Interdisciplinaridade, 2023)
This review presents the article “Harassment, Violence, Stress and Burnout in the Workplace”, written by Pedro Guilherme Basso Machado, published by the magazine Researcher of the Study and Research Group on Stress and Burnout - GEPEB. The article presented by the author seeks to understand harassment, violence, stress and burnout in the workplace, showing its consequences. Based on the notes revealed in the article, and the development of studies and actions on the subject, since there is a need for legal, ethical, environmental and relational actions that make it possible to face these issues and preserve the occupational health of these professionals.